2012
DOI: 10.1111/apa.12005
|View full text |Cite
|
Sign up to set email alerts
|

Differences in insulin resistance markers between children born small for gestational age or born preterm appropriate for gestational age

Abstract: The higher fasting insulin level in the SGA children, adjusted for BMI, could indicate peripheral insulin resistance. Preterm born children had reduced suppression of IGFBP-1 during OGTT, suggesting hepatic insulin resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 35 publications
2
26
1
Order By: Relevance
“…In studies of individuals born SGA at term (defined as BW SDS below −2 SDS), signs of insulin resistance have been detected in children (5) and at young adulthood (6). In our group of children born SGA at term (defined as BW SDS below −2 SDS), we have recently found higher insulin levels compared with the controls when adjusted for BMI, indicating early signs of a peripheral insulin resistance (7).…”
Section: Introductionmentioning
confidence: 48%
See 2 more Smart Citations
“…In studies of individuals born SGA at term (defined as BW SDS below −2 SDS), signs of insulin resistance have been detected in children (5) and at young adulthood (6). In our group of children born SGA at term (defined as BW SDS below −2 SDS), we have recently found higher insulin levels compared with the controls when adjusted for BMI, indicating early signs of a peripheral insulin resistance (7).…”
Section: Introductionmentioning
confidence: 48%
“…The characterizations and the modes of selection for the children (7) and the adult women (23) were previously described in detail. In brief, of 257 children consequently born at the Karolinska University Hospital between the years 1990 and 1993 and invited to take part in a follow-up study, 105 excepted to participate and blood values were obtained in 76 subjects (7).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In their study, the authors found that SGA infants had higher insulin levels and insulin resistance than their controls, suggesting peripheral insulin resistance. Also, the authors found that preterm infants had an attenuation in insulin-like growth factor-binding protein-1 (IGFBP-1) response during an oral glucose tolerance test (OGTT), suggesting a hepatic insulin resistance 33. Similarly, in a study of young adults born prematurely and SGA, Rotteveel et al43 found that preterm SGA adults have increased triglycerides and insulin during a mixed meal test.…”
Section: Metabolic Syndrome and Insulin Resistancementioning
confidence: 97%
“…In developing countries, the most common cause of asymmetrical IUGR remains caloric restriction or undernutrition. In developed countries, asymmetrical IUGR remains a problem in poverty stricken areas15 and it is associated with the hypertension spectrum,31,32 maternal diabetes, and vascular-related disorders such as lupus and smoking 33…”
Section: Iugr and Insulin Secretionmentioning
confidence: 99%